The effects of background music on English reading comprehension for English foreign language learners: evidence from an eye movement study - Su, Yankui; He, Meiling; Li, Rongbao (Frontiers in Psychology, 2023)
Based on the previous literature, the present study examines the effects of background music on English reading comprehension by eye tracking technique. All the participants were selected from a foreign language college, and all of them were sophomore who majored in English. The experiment in this study was a 2 (music tempo: fast and slow) × 2 (Text difficulty: difficult and easy) × 2 (background music preference: high and low) mixed design. Both musical tempo and English reading passage are within-subject factors, and the level of music listening preference is a between-item factor. The result showed that the main effect of the music tempo was statistically significant, which indicated that participants read texts more quickly in the fast tempo music condition than in slow tempo music condition. And the main effect of the text difficulty was statistically significant. Besides, the interaction between the text difficulty and music tempo was statistically significant. The music tempo had a greater effect on easy texts than on difficult texts. All the results of this study revealed that it is beneficial for people who have stronger preference for music listening to conduct English reading task with fast tempo music. It is detrimental for people who have little preference for background music listening to complete difficult English reading task with slow tempo music.